Roles for the 8-Oxoguanine DNA Repair System in Protecting Telomeres From Oxidative Stress - De Rosa, Mariarosaria; Johnson, Samuel A.; Opresko, Patricia L. (Frontiers in Cell and Developmental Biology, 2021)
Telomeres are protective nucleoprotein structures that cap linear chromosome ends and safeguard genome stability. Progressive telomere shortening at each somatic cell division eventually leads to critically short and dysfunctional telomeres, which can contribute to either cellular senescence and aging, or tumorigenesis. Human reproductive cells, some stem cells, and most cancer cells, express the enzyme telomerase to restore telomeric DNA. Numerous studies have shown that oxidative stress caused by excess reactive oxygen species is associated with accelerated telomere shortening and dysfunction. Telomeric repeat sequences are remarkably susceptible to oxidative damage and are preferred sites for the production of the mutagenic base lesion 8-oxoguanine, which can alter telomere length homeostasis and integrity. Therefore, knowledge of the repair pathways involved in the processing of 8-oxoguanine at telomeres is important for advancing understanding of the pathogenesis of degenerative diseases and cancer associated with telomere instability. The highly conserved guanine oxidation (GO) system involves three specialized enzymes that initiate distinct pathways to specifically mitigate the adverse effects of 8-oxoguanine. Here we introduce the GO system and review the studies focused on investigating how telomeric 8-oxoguanine processing affects telomere integrity and overall genome stability. We also discuss newly developed technologies that target oxidative damage selectively to telomeres to investigate roles for the GO system in telomere stability.